2019
DOI: 10.7567/1347-4065/ab09c8
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a nanostructured TiO2 photocatalyst using He plasma-irradiated tungsten and ethylene gas decomposition

Abstract: Decomposition of ethylene gas by a photocatalyst is an environmentally friendly and sustainable process. We fabricated titanium dioxide thin films deposited on nanostructured tungsten substrates formed by exposure to helium plasma and evaluated their photocatalytic performance. The nanostructures were maintained even after sputtering and annealing, and the proportion of tungsten inside the thin film increased with increasing oxidation temperature. The photocatalytic activity was improved due to formation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…19) Photocatalytic activity of He plasma induced nanostructures have been investigated on (partially) oxidized W, [20][21][22][23] vanadium, 24) niobium, 25) iron 26) and Ti. 27) In this study, we use He plasmas to induce morphology changes in micro-and nano-meter scales, and photocatalytic performance of those fabricated materials to degrade ethylene is measured. Recently, it was shown that TiO 2 thin layer formed on He induced nanostructured W increased the decomposition of ethylene via photocatalytic decomposition.…”
mentioning
confidence: 99%
“…19) Photocatalytic activity of He plasma induced nanostructures have been investigated on (partially) oxidized W, [20][21][22][23] vanadium, 24) niobium, 25) iron 26) and Ti. 27) In this study, we use He plasmas to induce morphology changes in micro-and nano-meter scales, and photocatalytic performance of those fabricated materials to degrade ethylene is measured. Recently, it was shown that TiO 2 thin layer formed on He induced nanostructured W increased the decomposition of ethylene via photocatalytic decomposition.…”
mentioning
confidence: 99%
“…83) At present, photocatalysts such as Ti-O, TiO 2 , and nitrogen-doped TiO 2 , and the antiviral activity of visible-light-sensitive Cu(II) and Fe(III) nanocluster-grafted TiO 2 have been reported by Miyaguchi et al 84,85) and Kajita and colleagues. 86,87) There have also been reports of the plasma-assisted coating of photocatalytic films on surfaces. [88][89][90] In terms of other metal oxides, the photocatalytic activity of nanostructured tungsten oxides was reported by Feng et al 91) There have also been reports of silver-doped ZnO, 92) ZnS and ZnO films, 93) and Fe 2 O 3 nanotubes and Cu 2 O.…”
Section: Antibacterial and Antiviral Coating Of Copper Etcmentioning
confidence: 99%
“…Among these methods, He plasma treatment is a novel method, which forms fiberform nanostructures (FNs) called fuzz on various metals including tungsten, molybdenum, rhenium, rhodium, tantalum, platinum, niobium, and V. [ 5,20–25 ] The process is a bottom‐up process accompanied by the growth of He bubbles on the top surface layer (thickness of 100–200 nm) and the formation and diffusion of adatoms. [ 26–30 ] Application of oxidized fuzz has been studied including the application of tungsten trioxides (WO3) as gas sensors [ 31–36 ] WO3, iron oxides, [ 37,38 ] titania, [ 39,40 ] and V oxides [ 5 ] as photoelectrodes. On the fuzzy oxides, in addition to the increase in the active area to be used for reactions, [ 38 ] other positive aspects of the He treatment have been revealed, such as the formation of oxygen vacancies, [ 36 ] which can improve photoelectrochemical (PEC) performance, and stabilization of the anatase structure of titania.…”
Section: Introductionmentioning
confidence: 99%
“…For example, pulsed laser deposition (PLD), [9] magnetron sputtering, [10] chemical vapor deposition (CVD), [11] plasma-enhanced CVD, [12] solgel method, [13,14] and sol-gel dip coating [15] were used to deposit thin films; hydrothermal process, [16] thermal pyrolysis, [17] electrospinning, [18] ion beam sputtering, [19] and helium (He) plasma treatment [5] were used for nanostructuring.Among these methods, He plasma treatment is a novel method, which forms fiberform nanostructures (FNs) called fuzz on various metals including tungsten, molybdenum, rhenium, rhodium, tantalum, platinum, niobium, and V. [5,[20][21][22][23][24][25] The process is a bottom-up process accompanied by the growth of He bubbles on the top surface layer (thickness of 100-200 nm) and the formation and diffusion of adatoms. [26][27][28][29][30] Application of oxidized fuzz has been studied including the application of tungsten trioxides (WO 3 ) as gas sensors [31][32][33][34][35][36] WO 3 , iron oxides, [37,38] titania, [39,40] and V oxides [5] as photoelectrodes. On the fuzzy oxides, in addition to the increase in the active area to be used for reactions, [38] other positive aspects of the He treatment have been revealed, such as the formation of oxygen vacancies, [36] which can improve photoelectrochemical (PEC) performance, and stabilization of the anatase structure of titania.…”
mentioning
confidence: 99%